Assessment of Non-Stationary Processes in Unstable Operating Modes of Pumping Stations (Eurasian Research Bulletin, 2023)
Assessment of the impact of wave processes during transient and emergency operating conditions of the hydraulic system of reclamation pumping stations, which inevitably lead to a decrease in the strength limits of pipelines, the accumulation of metal fatigue, especially in places that are concentrators of fatigue stresses in pipeline metal, which increases the likelihood of accidents with pipeline ruptures. They justified the need to model probable emergency situations of pump operation in the water supply system in order to establish the possibility of using modern methods for calculating transient processes in pumping stations of reclamation systems. Based on the modeling results, it was established that in the pressure pipeline of reclamation pumping stations, during an emergency shutdown of the pump, there is a high probability of a break in the continuity of the water flow. It was calculated that installing a pressure stabilizer on the pressure pipeline with one damping chamber in direct proximity to the pump, check valves and shut-off valves of water pipelines (sources of disturbance) will reduce the amplitude of pressure fluctuations in the pipeline by 2,5...2,6 times and lead to more rapid attenuation of wave processes due to a change in sign-alternating shock loads to smoother ones, extended over time. It was established that emergency protection of the pipeline system using wave pressure stabilization technology will protect pipelines from ruptures in the event of emergencies; ensure energy savings by reducing the accident rate on pipelines and increase the uninterrupted provision of services to the population and water supply enterprises.